Unlocking Logistics Efficiency: The Strategic Role of Third-Party Logistics (3PL) in Indonesia’s Manufacturing Sector - Zulkarnain, Ahnis (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the impact of third-party logistics (3PL) outsourcing on the efficiency of Indonesia’s manufacturing sector, a key industry burdened by high logistics costs, infrastructural deficiencies, and regulatory fragmentation. The objective is to determine whether 3PL adoption enhances logistics performance by reducing costs, improving scalability, and mitigating operational inefficiencies. Employing a mixed-method approach, the research draws on secondary data from industry reports and academic literature. Key performance indicators such as logistics cost structures, response time to demand changes, and integration risk severity were analyzed to compare in-house logistics operations with outsourced 3PL models. Results demonstrate significant cost reductions through 3PL - 41.7% in warehousing, 40% in transportation, and 20% in labor alongside enhanced scalability and responsiveness. 3PL providers achieved higher adaptability in managing demand fluctuations, requiring only 3 weeks to scale up operations versus 8 for in-house logistics. However, risks including IT system mismatches (72% frequency), SLA misalignments, and data security concerns were also prevalent. The findings confirm that 3PL offers a viable solution for improving logistics efficiency, provided that integration risks are carefully managed. Long-term 3PL partnerships yield financial as well as strategic benefits, including access to advanced technologies and greater operational agility. For Indonesia to fully realize the advantages of 3PL, coordinated efforts are needed from both the government and private sector to address regulatory bottlenecks, improve infrastructure, and support digital transformation.